Dynamic stability evaluation method of mine goaf slopes - Yan DU; Hongda ZHANG; Mowen XIE; Yujing JIANG; Ming ZHANG; Beining JIA (工程科学学报)
The collapse and damage of inclined rock and soil masses caused by subsidence in mining goaf areas pose serious geological risks. These hazards are not only highly destructive and widespread but also occur suddenly, endangering mine operations and human safety. Traditional stability evaluation methods often overlook the variations in thrust caused by the settlement of goaf blocks at the leading edge locking section, making it difficult to dynamically evaluate mine slope stability. This limits the effectiveness of early warning and prevention strategies for geological disasters in mines. To address these challenges, this study introduces a dynamic stability evaluation method tailored for mine slopes, targeting the landslide formation mechanisms in mining goaf areas. The first involves constructing a settlement analysis model for the goaf areas to calculate the settlement range of the rock mass above the goaf and the resulting impact forces. The proposed model helps analyze how settlement affects the stress field of slopes. Therefore, the traditional unbalanced thrust method is modified. During stability evaluation, the safety factor of the slope’s locking section under the subsidence effect of the goaf was analyzed. When the safety factor of the locking section (SFk) is less than 1, the residual strength needs to be considered to calculate the overall safety factor (SF) of the slope. If SFk exceeds 1, the section remains intact, allowing the SF to be calculated under original working conditions. The Jiweishan case in Wulong, Chongqing, illustrates the limitations of traditional methods, which neglected the settlement and locking section damage, overestimating the safety factor at 1.355. The improved method, accounting for these effects, found the locking section’s safety factor at 0.667, indicating damage and an overall landslide safety factor of 0.979. This finding aligns with the observed failure and instability mechanism of the mine goaf landslide. When the weight of the settlement slope at the rear edge is large, settlement causes instantaneous shear failure of the landslide locking section, substantially reducing the stability of the Jiweishan landslide. The settlement–horizontal displacement ratio (SHDR) of the slope is crucial in dynamic stability analysis for goaf areas. An SHDR greater than 0.73 indicates significant stability variations, leading to instability under working conditions previously deemed safe. This improved method offers a more accurate assessment of mine slope stability by considering goaf settlement and locking section damage, providing a valuable tool for managing similar geological disasters.